The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fmicb.2014.00506
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics defines the core genome of the growing N4-like phage genus and identifies N4-like Roseophage specific genes

Abstract: Two bacteriophages, RPP1 and RLP1, infecting members of the marine Roseobacter clade were isolated from seawater. Their linear genomes are 74.7 and 74.6 kb and encode 91 and 92 coding DNA sequences, respectively. Around 30% of these are homologous to genes found in Enterobacter phage N4. Comparative genomics of these two new Roseobacter phages and 23 other sequenced N4-like phages (three infecting members of the Roseobacter lineage and 20 infecting other Gammaproteobacteria) revealed that N4-like phages share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 61 publications
5
61
0
Order By: Relevance
“…None of these analyses showed any match between R5C and viral spacer sequences within CRISPRs. When the R5C genes were searched against the POV and GOS databases, we found that their homologs were widespread from coastal regions to open oceans, similar to the previously shown genomic recruitment of N4-like roseophages [29]. A more detailed analysis showed that similar levels of identity (coastal, 22.2–90.0%; intermediate, 22.0–81.8%; open ocean, 22.6–83.3%) were found in different kinds of environment in the POV.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…None of these analyses showed any match between R5C and viral spacer sequences within CRISPRs. When the R5C genes were searched against the POV and GOS databases, we found that their homologs were widespread from coastal regions to open oceans, similar to the previously shown genomic recruitment of N4-like roseophages [29]. A more detailed analysis showed that similar levels of identity (coastal, 22.2–90.0%; intermediate, 22.0–81.8%; open ocean, 22.6–83.3%) were found in different kinds of environment in the POV.…”
Section: Resultssupporting
confidence: 74%
“…It has been shown that roseophages contain a considerable degree of genomic variability [29,33]. However, compared with the biogeographical, physiological and ecological diversity of Roseobacter , the range of roseophages studied so far remains relatively narrow.…”
Section: Introductionmentioning
confidence: 99%
“…also cluster with the host species. Overall, the phylogeny of N4-like phage genotypes based on the DNA pol gene is concordant with that previously reported based on concatenated core genes of N4-like phages (24). The congruency between the DNA pol phylogeny and the host taxonomy suggests N4 phages originated from a common ancestor and coevolved with their hosts.…”
Section: Resultssupporting
confidence: 71%
“…To do this, we screened a library of viral concentrates collected from the Chesapeake Bay over the course of 2 years (2004 and 2005) through the Microbial Observatory for Virioplankton Ecology Project (http://www.virusecology.org/MOVE/Home.html) using a PCR primer set targeting conserved regions of the DNA pol genes of N4-like phages. The DNA pol gene is one of the 14 conserved core genes of N4-like phages (24), making it a valuable diagnostic marker for culture-independent surveys. A total of 56 viral samples, which cover four seasons and the full transect of the Bay, were tested.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation